2006
DOI: 10.1007/s10620-005-9012-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Response Is Associated with Elevated Plasma Interleukin-1 Receptor Antagonist During Selective Granulocyte and Monocyte Apheresis in Patients with Ulcerative Colitis

Abstract: Depletion of granulocytes and monocytes (GM) by selective apheresis (GMA) with an Adacolumn exerts an anti-inflammatory effect in patients with ulcerative colitis (UC) or rheumatoid arthritis. However, the mechanism of the anti-inflammatory effect of GMA is not fully understood yet. We investigated the effect of GMA on the plasma concentration of interleukin-1 receptor antagonist (IL-1ra), a potent anti-inflammatory cytokine. Twenty-six patients with active UC received GMA at one session per week for 5 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
9
1
Order By: Relevance
“…Further, 26 patients (65%) remained in clinical as well as endoscopic remission for an average of 14 months, ranging from two to 58 months. These remission values (65%) are in line with other studies, however with more homogenous patient selection [45,50]. All 26 patients remained steroid-free during the follow-up period.…”
Section: Discussionsupporting
confidence: 90%
“…Further, 26 patients (65%) remained in clinical as well as endoscopic remission for an average of 14 months, ranging from two to 58 months. These remission values (65%) are in line with other studies, however with more homogenous patient selection [45,50]. All 26 patients remained steroid-free during the follow-up period.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study we found that ulinastatin did not inhibit GM adsorption to cellulose acetate beads, and that 10 000 units/mL of ulinastatin augmented the release of IL‐1ra induced by GM adsorption. Ulinastatin and cellulose acetate beads are separately used for patients with ulcerative colitis, and IL‐1ra release is correlated with clinical efficacy (15,17); thus, the present study demonstrates the feasibility of combination therapy with ulinastatin and GMA.…”
Section: Discussionmentioning
confidence: 53%
“…Other investigators have reported elevated blood levels of antiinflammatory substances including IL-1 receptor antagonist (IL-1ra), IL-10, soluble TNF-a receptors I and II, CD10 -granulocytes, TLR2 low granulocytes, CD25 hi CD4 ? regulatory T cells, and reduced circulating dendritic cells following GMA [15][16][17][18][19][20][21][22][23][24]. These observations have broadened the actions of GMA.…”
Section: Introductionmentioning
confidence: 99%